Passalidae (Coleoptera: Scarabaeoidea) of the Greater and Lesser Antilles - Jiménez-Ferbans, Larry; Reyes-Castillo, Pedro; Schuster, Jack C. (Zootaxa, 2015)
We present a synthesis of the state of knowledge concerning the species of Passalidae (Coleoptera) of the West Indies and we present a key to the species. The recently described genus Antillanax Boucher renders the subgenus Passalus (Pertinax) Kaup paraphyletic, therefore we place Antillanax in synonymy with Passalus (Pertinax) and we propose a new combination for Passalus (Pertinax) doesburgi (Boucher). The island richest in species is Hispaniola, with five species, three of them endemic. Excluding Trinidad and Tobago, the passalid fauna of the West Indies comprises 13 species; this is low richness, but with high endemism (50%), especially for the Greater Antilles.